Sains dan Teknologi Dalam Ketamaduan Islam : Analisa Epistemologi dan Metodologi - Zainul Bakir Fauzi (STIKes Ibnu Sina Ajibarang, 2024)
Science and technology have evolved in tandem with the development pattern of human civilization in this universe. The history of human civilization requires the effort of the manifestation of values within the scope of their own perspective. The above statement can be proven by a strong backing with the meaning of science and technology itself, it is a value and includes cultural views formed by human beings themselves.